Review on development of Traditional Chinese Medicine nursing clinics (中医护理门诊发展现状探讨) - XI Yawei (习亚炜); DING Fuyu (丁福郁) (中西医结合护理)
People are paying more attention on disease prevention as the economy growth and environment change, and the focus of health care has shifted from management of disease to prevention and healthy living. Nursing interventions based on Traditional Chinese Medicine theories play an increasing important role in disease prevention and treatment, and the nurse-led Traditional Chinese Medicine nursing clinic emerges as the times require. This paper analyzed the development and current situation of Traditional Chinese Medicine nursing clinics, and provided suggestions for sustainable development of Traditional Chinese Medicine nursing clinics. (随着社会经济水平的不断提高和人们生活环境的不断变化, 人们对于疾病的预防越来越重视, 医学的重心由疾病治疗向疾病预防转变, 在中医基本理论指导下的护理工作可以很好达到防病治病的作用, 由此, 以护士为主导的护理门诊应运而生。本文通过对护理门诊的发展现状进行分析, 并为中医护理门诊持续发展提供相关建议。)